TikTok to Learn English Vocabulary: Voices of Indonesian Learners from English Departments - Rita, Rita; Subekti, Adaninggar Septi (TEKNOSASTIK, 2024)
The present study aims to investigate the perspectives of learners from English departments on the use of TikTok for second/foreign language (L2) vocabulary learning. This study is a continuation of a preceding survey study involving 116 learners from 26 universities in ten different provinces in Indonesia. The participants of the present study were six selected learners from three universities taken from the preceding study. This study employed semi-structured interviews and the interview data were analysed using Thematic Analysis. From the Thematic Analysis, the study found three recurring themes. They perceived various English videos on TikTok to be useful to facilitate vocabulary learning. English content created by native speakers was also perceived positively as a good vocabulary-learning resource. Nevertheless, they also noted that the effectiveness of TikTok as a vocabulary learning media largely depended on whether learners could optimally use it for learning purposes. Based on the findings, it is suggested that teachers bring TikTok into the class to optimally use its potential and leverage its popularity among learners. By doing so, teachers can also facilitate learners not only to be passive users but also to produce English content they could post on the platform. It can potentially make learning more fun and meaningful for learners.